2021
DOI: 10.3389/fpls.2021.643213
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of MicroRNAs Involved in Mepiquat Chloride-Mediated Inhibition of Internode Elongation in Cotton (Gossypium hirsutum L.) Seedlings

Abstract: Mepiquat chloride (MC) is the most important plant growth retardant that is widely used in cotton (Gossypium hirsutum L.) production to suppress excessive vegetative growth and improve plant architecture. MicroRNAs (miRNAs) are important gene expression regulators that control plant growth and development. However, miRNA-mediated post-transcriptional regulation in MC-induced growth inhibition remains unclear. In this study, the dynamic expression profiles of miRNAs responsive to MC in cotton internodes were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…Altogether it can be concluded that PD treatment has the highest effect on internodes length; these retardant plays and important role on blocking gibberellins biosynthesis, which is the key product for cell elongation, and because of this effect internodes length are inhibited. In other studies, it was also reported that plant growth regulators can inhibit internodes growth in Gossypium hirsutum L. [53,54], Bougainvillea [55], Vigna radiata L. [56] and on Zinnia elegans [57].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether it can be concluded that PD treatment has the highest effect on internodes length; these retardant plays and important role on blocking gibberellins biosynthesis, which is the key product for cell elongation, and because of this effect internodes length are inhibited. In other studies, it was also reported that plant growth regulators can inhibit internodes growth in Gossypium hirsutum L. [53,54], Bougainvillea [55], Vigna radiata L. [56] and on Zinnia elegans [57].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA targets were computationally predicted using psRNATarget [ 47 ] with the default parameters. The expression level of each identified miRNA was calculated as transcripts per million (TPM) using the formula: mapped read count/total reads × 1,000,000 [ 71 ]. To assess the expression changes between tissues, three biological replicates were pooled based on the mean TPM values.…”
Section: Methodsmentioning
confidence: 99%
“…The coordination of the cotton source-sink relationship is not only a material relationship, but plant hormones may also be an important information regulation system [43]. The mechanism of DPC inhibiting the apical dominance of cotton is that it acts as an inhibitor of gibberellin (GA) and inhibits fruit branch elongation and plant height growth by reducing its own GA3 content in cotton tissue [44]. Specifically, it retards vegetative growth by inhibiting the activity of gibberellin involved in cell elongation, which inhibits the signaling pathways and disturbs GA homeostasis by upregulating site-specific genes that ultimately result in keeping the plant stature shorter [45].…”
Section: Chemical Topping Creates a Compact Plant Architecture By Aff...mentioning
confidence: 99%